Crossing the interdisciplinary border: A structural linguistics genre analysis - Mohan Rathakrishnan, Gurmit Singh Pertap Singh, (Opción, 2019)
This paper presents the steps taken to develop a specific teaching framework that fulfills the fundamental real-life context of the prospective legal practitioners, using the specific genre analysis approach which integrates a corpus-based approach and a structural linguistics analysis. The findings showed the use of specific moves and parts-of-speech by the legal practitioners, in order to prepare the selected genre. In conclusion, the findings from the present study highlighted a suitable teaching framework, deemed to be useful for the teaching of the content of the sales and purchase agreements.